2022
DOI: 10.1038/s41698-022-00319-y
|View full text |Cite
|
Sign up to set email alerts
|

Clinical prospects of WRN inhibition as a treatment for MSI tumours

Abstract: The discovery of synthetic lethal interactions with genetic deficiencies in cancers has highlighted several candidate targets for drug development, with variable clinical success. Recent work has unveiled a promising synthetic lethal interaction between inactivation/inhibition of the WRN DNA helicase and tumours with microsatellite instability, a phenotype that arises from DNA mismatch repair deficiency. While these and further studies have highlighted the therapeutic potential of WRN inhibitors, compounds wit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
6
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(6 citation statements)
references
References 83 publications
0
6
0
Order By: Relevance
“…MMR deficiency/MSI-H are clinically useful biomarkers for immunotherapy in multiple cancer types. Recent studies suggest that MSI-H may also be a good biomarker for WRN inhibitors ( Chan et al 2019 ; van Wietmarschen et al 2020 ), which are still under development ( Morales-Juarez and Jackson 2022 ). Our findings in this study suggest that MMR deficiency/MSI-H are also useful biomarkers to guide patient stratification for treatment with ATR inhibitors, which are already extensively tested in clinical trials ( Sundar et al 2017 ; Ngoi et al 2022 ).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…MMR deficiency/MSI-H are clinically useful biomarkers for immunotherapy in multiple cancer types. Recent studies suggest that MSI-H may also be a good biomarker for WRN inhibitors ( Chan et al 2019 ; van Wietmarschen et al 2020 ), which are still under development ( Morales-Juarez and Jackson 2022 ). Our findings in this study suggest that MMR deficiency/MSI-H are also useful biomarkers to guide patient stratification for treatment with ATR inhibitors, which are already extensively tested in clinical trials ( Sundar et al 2017 ; Ngoi et al 2022 ).…”
Section: Discussionmentioning
confidence: 99%
“…These findings suggest that inhibition of WRN may be an effective way to selectively kill MSI cancer cells harboring expanded (TA)ns. Indeed, WRN-specific inhibitors are being developed and their effects on MSI tumors are being assessed ( Morales-Juarez and Jackson 2022 ).…”
mentioning
confidence: 99%
“…In the past 4 yr, multiple studies have identified a unique addiction of human MSI-H cancers to the RECQ family helicase WRN ( Behan et al 2019 ; Chan et al 2019 ; Kategaya et al 2019 ; Lieb et al 2019 ; van Wietmarschen et al 2020 ; Picco et al 2021 ; Morales-Juarez and Jackson 2022 ), uncovering one of the most striking examples of synthetic lethality since PARP inhibition was shown to specifically kill homologous recombination-defective breast/ovarian cancers two decades ago ( Bryant et al 2005 ; Farmer et al 2005 ). This has led to a huge push from the pharmaceutical industry to develop clinical-grade WRN inhibitors.…”
mentioning
confidence: 99%
“…WRN encodes a DNA helicase and nuclease that functions in DNA replication, repair, and transcription [55][56][57] and has recently been identified as a SL vulnerability of MMR-deficient MSI cancers, including some colorectal, endometrial, gastric, and ovarian cancers 8,[58][59][60][61][62] . Although WRN was categorised as a drug target group II candidate by the Open Target Platform 45 (Methods), there are currently several drug development programs underway to target WRN 63,64 in MSI cancer; therefore, we re-classified it as a drug target group I and priority class A gene.…”
Section: Gi Prediction Scores and Target Tractability Assignments Pri...mentioning
confidence: 99%